Air pollutant removal by four sidewalk tree species in the largest city in Taiwan. Issue 5 (31st August 2022) - Ku, Po‐Jung; Chang, Chung‐Te; Jien, Shih‐Hao; Hseu, Zeng‐Yei; Lin, Teng‐Chiu
Abstract: Air pollutants pose risks to human health, especially in densely populated cities. We compared the interception of suspended particles and metal elements by four sidewalk tree species with different leaf surface wettability (based on contact angle), leaf area, and phenology in Taipei, Taiwan. Suspended particles were enriched 2.0‒2.5 times in throughfall relative to rainfall due to wash‐off of suspended particles deposited on leaf surfaces during rainless periods. The enrichment in throughfall was greater in tree species with larger leaf areas. Despite greater concentrations of suspended particles in rainfall during the low‐leaf‐area period, enrichment was greater in the high‐leaf‐area period, indicating that leaf area was a key factor affecting canopy interception of pollutants. Throughfall enrichment of suspended particles positively correlated with water quantity, indicating that air pollutants intercepted by tree canopies were not fully washed off by rainfall. Annually, ∼830 g of suspended particles were intercepted and washed off from one tree canopy, with a crown area of 42 m 2 . Scaling up, a rough estimate of 72.7 Mg of suspended particles were intercepted annually by the 90, 000 sidewalk trees in Taipei City. Copper, chromium, and aluminum were enriched in throughfall compared with rainfall. However, lead was depleted in throughfall, indicating greater interception than wash‐off. Based on our results, leaf area and length of foliated period are key characteristics affecting canopy interception of particulate matter and associated metal elements, whereas leaf surface wettability is of secondary importance. Core Ideas: Leaf area and length of foliated period are key to pollutant interception by trees. Annually, ∼73 Mg of suspended particles were intercepted and washed off from the 90, 000 sidewalk trees of Taipei. Much of canopy intercepted Pb was not washed off by rainfall.